P R O M O S I K E S E H A T A N P A D A P E N D E R I T A D E M A M B E R D A R A H D E N G U E M E L A L U I P E N Y U L U H A N P A D A M A S Y A R A K A T D I D E S A S I G U C I K E C A M A T A N S T M H I L I R K A B U P A T E N D E L I S E R D A N G - Evalina Manurung; Sri Sudewi Sitio; Tedty Rohaya Tinambunan; Sulastri Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Mental health is a condition of subjective feeling of well-being, a self-assessment of feelings which includes aspects of self-concept, fitness and the ability to control oneself. The purpose of conducting counseling in Siguci Village, STM Hilir Subdistrict, Deli Serdang Regency is to implement a community or community health diagnosis which essentially identifies, formulates and compiles public health problems. Developing a program to handle public health problems that is promotive and preventive in nature and is a learning process to gain professionalism skills. The approach to health problems is carried out through a survey method with a Cross Sectiona l approach based on the stages of community diagnosis. Community Diagnosis is defined as a description or description of public health and the factors that affect the health of the local community both quantitatively and qualitatively. Based on primary data, the risk factors for the occurrence of dengue hemorrhagic fever in Dusun I Siguci Village are mostly caused by Clean and Healthy Lifestyle (PHBS), Waste Management, Community Waste Disposal and a priority for health problems is the incidence of dengue hemorrhagic fever.